Personality disorders in a sample of social phobics (Archives of Clinical Psychiatry, 2006)
The aim of this study was to investigate if other comorbid personality disorders, other than avoidant personality disorder, occur among social phobics. Twenty-two patients with a social phobia diagnosis according to DSM-III-R criteria were evaluated by using the Minnesota Multiphasic Personality Inventory (MMPI), the Structured Interview for DSM-III-R Personality Disorders (SIDP-R) and the Present State Examination (PSE). Fourteen patients (64%) of the sample received at least one personality disorder diagnosis - all of them received avoidant personality disorder diagnosis. One half of personality disordered patients showed two or more personality disorders. Paranoid personality disorder was diagnosed in six patients (27%). Ten patients (46%) evaluated with MMPI had a pathological score in the Paranoia (Pa) scale. Other pathological personality traits were also present in Depression (D), Hysteria (Hy) and Introversion-Extroversion (Si) scales of MMPI. PSE no delusional ideas of reference (IR) occurred in nineteen patients. Paranoid personality disorder was diagnosed in a higher frequency in this study than in most of the other studies, which analyzed social phobics. This appears to have occurred because of not very specific diagnostic criteria overlapping as well as self-reference and paranoid personality traits, such as hypersensitivity and concern about other peoples opinions.